150-kD oxygen-regulated protein is expressed in human atherosclerotic plaques and allows mononuclear phagocytes to withstand cellular stress on exposure to hypoxia and modified low density lipoprotein. - Tsukamoto, Y (1996)
The 150-kD oxygen-regulated protein (ORP150) was initially characterized based on its selective expression in astrocytes subjected to oxygen deprivation (Kuwabara, K., M. Matsumoto, J. Ikeda, O. Hori, S. Ogawa, Y. Maeda, K. Kitagawa, N. Imuta, K. Kinoshita, D.M. Stern, et al. 1996. J. Biol. Chem. 279:5025-5032). We have found that exposure of cultured human aortic smooth muscle cells and mononuclear phagocytes (MPs) to hypoxia (pO2 approximately 12-14 torr) induces ORP150 transcripts and production of the antigen, whereas incubation with either hydrogen peroxide, sodium arsenite, heat shock, or 2-deoxyglucose was without effect. Tissue extracts prepared from human atherosclerotic lesions demonstrated expression of ORP150 mRNA and antigen, vs lack of ORP150 in samples from nonatherosclerotic areas. In situ hybridization using ORP150 riboprobes showed the mRNA to be predominantly [correction of predominately] present in macrophages in in atherosclerotic plaques. Furthermore, autoantibody to ORP150 was demonstrated in the serum of patients with severe atherosclerosis, consistent with inducible in vivo expression of ORP150. Introduction of antisense oligonucleotide for ORP150 selectively diminished hypoxia-mediated induction of ORP150 antigen and reduced the viability of hypoxic MPs, especially in the presence of modified (oxidized/acetylated) LDL. In support of a role for ORP150 in the MPs' response to the microenvironment of an atheroma, the presence of oxidized LDL enhanced by approximately 10-fold ORP150 expression in hypoxic cultures. These data indicate that cells of the atherosclerotic vessel wall express ORP150 as part of a protective mechanism, potentially triggered by local hypoxia/hypoxemia and augmented by modified lipoproteins. The presence of antibody to ORP150 in sera of patients with severe atherosclerosis emphasizes the possibility that ORP150 may be a marker of vascular pathology.